All Days 2012
DOI: 10.2118/161348-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Production Performance of the Hydraulically Fractured Horizontal Wells

Abstract: The emergence of the ultra-low permeability formations, such as Marcellus Shale, as a target of exploration and development has created new challenges for resource development. To achieve economic production from shale formations massive stimulation treatments are required. Horizontal wells are the most effective in providing access to the formation to perform multi-stage hydraulic fracturing treatments. The limited field experience with multiple hydraulic fractures in horizontal wells indicates that significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Also, in later production time, harmonic decline (b=1) can be observed (Belyadi, F. et al, 2012). (Belyadi, F. et al, 2012). shows the 30 years simulated production profile which was closely fitted to Arps decline curve model.…”
Section: Objective 3: Impact Of Desorption On the Production Decline mentioning
confidence: 65%
See 2 more Smart Citations
“…Also, in later production time, harmonic decline (b=1) can be observed (Belyadi, F. et al, 2012). (Belyadi, F. et al, 2012). shows the 30 years simulated production profile which was closely fitted to Arps decline curve model.…”
Section: Objective 3: Impact Of Desorption On the Production Decline mentioning
confidence: 65%
“…Moreover, Table below shows that in the early time, linear flow regime (b=2) can be seen. Also, in later production time, harmonic decline (b=1) can be observed (Belyadi, F. et al, 2012). (Belyadi, F. et al, 2012).…”
Section: Objective 3: Impact Of Desorption On the Production Decline mentioning
confidence: 95%
See 1 more Smart Citation
“…The first is due the interference between the stages and second is due to the impact of the reservoir exterior. Belyadi, F. et al (2012) provided an insight into the long term production performance for horizontal wells with multiple hydraulic fractures in ultra-low permeability formations. They applied the production decline analysis to the horizontal wells with the multiple hydraulic fracture stages.…”
Section: Figure 10 Diagnostic Plot Of Derivative Of 1/q Aginst Time mentioning
confidence: 99%
“…However, the latter part shows a decline curve that is characterized by b =1, which is the harmonic decline. Belyadi, F. et al (2012) concluded that the approach of using a single value for the decline exponent (b) cannot provide reliable results to characterize the entire production period. This is due to the changes in flow regime.…”
Section: Figure 10 Diagnostic Plot Of Derivative Of 1/q Aginst Time mentioning
confidence: 99%